Chemical attributes of Brazilian Cerrado soil under different management systems - Ramos, Tatiana Vieira; Santos, Leovigildo Aparecido Costa; de Souza, Wander Gomes; de Souza, Kellen Rabello; Lima, Nauara Lamaro; Guimarães, Luanna Elis; Brandão, Daniel Cardoso; da Silva, Jaqueline Pinheiro; Gonçalves, Rosana Alves; Gonçalves, Bruno Bastos; Arruda, Everton Martins; Calil, Francine Neves; et al. (Southern Cross Publishing, 2018)
Agricultural use and management systems in tropical soils of the Brazilian Cerrado may directly influence its chemical properties, in the conventional cultivation systems with pastures or grains, as well as in areas with a crop-livestock-forest integration system. Thus, the objective was to evaluate the chemical attributes of the soil under different use and management systems. The research was carried out at Boa Vereda Farm, in the state of Goiás, Brazil. The experimental design was completely randomized with a 5 x 3 factorial arrangement divided into five production systems: (1) among the rows of Eucalyptus (CLFI), (2) within the rows of Eucalyptus (CLFI), (3) in conventional agricultural monoculture, (4) pasture, and (5) - natural Cerrado (control treatment). Samples were collected in three soil depths (0-0.5; 0.5-0.1 and 0.1-0.2 m), with four replicates each. Among the chemical properties of the soil studied, the organic matter, calcium, magnesium and potassium contents, base saturation, and cation exchange capacity, are higher in the soil with natural Cerrado. The area of agricultural monoculture showed the highest levels of phosphorus and copper, but has the lower levels of organic matter in the soil. The chemical properties of the soil were similar in the CLFI system, regardless of the evaluation point (within or among rows). The chemical properties of the soil evaluated were similar between the pasture cultivated in CLFI and the conventional system. Therefore, the land use and management system do not directly influence the chemical properties of the soils evaluated.
Keywords: Agrosilvopastoral; Fertility; Grain production; Pasture